2004
DOI: 10.1177/002214650404500102
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stressors and Daily Hassles: Unique and Interactive Relationships with Psychological Distress

Abstract: Using daily telephone interviews of a U.S. national sample of adults, aged 25-74 (N = 1,031), the present analyses draw from theories of the stress process and recent research to examine how chronic role-related stressors and daily hassles affect psychological distress. Four separate hypotheses are examined. The first explores the association between chronic stressors and daily hassles. The second tests whether daily hassles function as an intervening variable between chronic stressors and psychological distre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
188
2
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(206 citation statements)
references
References 61 publications
8
188
2
8
Order By: Relevance
“…Furthermore, a study conducted outside of a healthcare context focussing on psychological distress found measures of chronic stressors to be associated with more daily hassle reports [46]. The authors of this study however, suggested that although they share a common context, daily hassles and chronic stressors have a different aetiology, and their findings supported the rationale for measuring chronic stressors as distinct from daily hassles.…”
Section: Contribution Of the Researchmentioning
confidence: 53%
“…Furthermore, a study conducted outside of a healthcare context focussing on psychological distress found measures of chronic stressors to be associated with more daily hassle reports [46]. The authors of this study however, suggested that although they share a common context, daily hassles and chronic stressors have a different aetiology, and their findings supported the rationale for measuring chronic stressors as distinct from daily hassles.…”
Section: Contribution Of the Researchmentioning
confidence: 53%
“…Some have suggested that smaller, daily stressors may actually have a greater impact on overall functioning than major life events (DeLongis, Coyne, Dakof, Folkman, & Lazarus, 1982), though everyday stressors and chronic stressors do appear to interact (Serido, Almeida, & Wethington, 2004). Indeed, evidence suggests that major life stressors may sensitize individuals, thereby exacerbating their responses to smaller events in the future (Pillow, Zautra, & Sandler, 1996).…”
Section: The Role Of Age In Financial Stressmentioning
confidence: 99%
“…SST suggests that as the end of life approaches, preference is given to satisfying social and emotional goals, as well as regulating one's emotions such that positive emotional experiences are maximized and negative emotional experiences are minimized. Considerable evidence exists showing that reported exposure to daily stressors is associated with increases in negative affect (Bolger, DeLongis, Kessler & Schilling, 1989;Bolger & Schilling, 1991;Marco & Suls, 1993;Smyth, Ockenfels, Porter, Kirschbaum, Hellhammer & Stone, 1998;van Eck, Nicolson & Berkhof, 1998;Zautra, Affleck, Tennen, Reich & Davis, 2005), and daily distress (Almeida & Kessler, 1998;Bolger & Zuckerman, 1995;Grzywacz et al, 2004;Serido, Almeida & Wethington, 2004). Because our emotions are inextricably linked to our experiences, daily stress research can help to understand the contexts associated with daily emotional experiences, as well as the role daily stressors play in emotional experiences across the adult lifespan.…”
Section: Introductionmentioning
confidence: 99%